Kepimpinan beretika dan kecemerlangan organisasi dalam perkhidmatan awam - Zaharah Hassan,; Abu Daud Silong,; Nazri Muslim, (Universiti Kebangsaan Malaysia, 2009)
Leadership is a very important factor in determining organisations’ effectiveness. The values uphold by leaders will influence their conduct as ethical leaders or not. What are ethical behaviours? Why are they important? What are the values and behaviours that are being inculcate among public sectors workers? How is it done? What are the strategies employed to enhance ethical behaviours? Analysis shows that despite numerous efforts done by the top managements, the result are not very encouraging because there is no comprehensive plan to educate public sector employees about ethics